Drug delivery nano-scaffold for effective implantation in orthopedic applications. (2022) - Tsiapla, Aikaterini-Rafailia; Gravalidis, Christoforos; Karagkiozaki, Varvara; Bakola, Veroniki; Logothetidis, Stergios
Abstract: The number of patients in need of a total hip replacement is increased constantly. However, infections and acute-chronic inflammations associated with implants are considered to be two of the major causes of implant failure after an invasive orthopedic surgery. In this work, a drug delivery nanoplatform system was fabricated of vancomycin loaded polycaprolactone scaffolds and dexamethasone loaded cellulose acetate scaffolds via dual syringe electrospinning system. Scanning electron microscopy applied to prove the scaffolds' successful fabrication. The controllable release of both drugs assessment and the mass loss estimation were examined through drug release kinetics and degradation studies, respectively. In vitro investigation of non-woven fibrous meshes-coated titanium implants took place and showed good cell adhesion and proliferation. Due to the results, these drug delivery nanoplatforms may be a promising approach, to prevent and treat not only orthopedic implant-associated infections, but also acute and chronic inflammations.